MATHEMATICAL MODEL OF BENDING-TORSIONAL VIBRATIONS OF THE MECHANICAL SYSTEM "BATAN MECHANISM" - Dremova Nadezhda Vasilievna (Journal Park Publishing, 2022)
The article deals with the dynamic characteristics of the batan mechanism - its natural frequencies during bending-torsional vibrations. An assessment of the results of theoretical and experimental studies is given.
Keywords: reed; batanny mechanism; bending-torsional vibrations